2001
DOI: 10.1038/35074073
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical variations in seismic velocity at the top of the Earth's inner core

Abstract: Knowledge of the seismic velocity structure at the top of the Earth's inner core is important for deciphering the physical processes responsible for inner-core growth. Previous global seismic studies have focused on structures found 100 km or deeper within the inner core, with results for the uppermost 100 km available for only isolated regions. Here we present constraints on seismic velocity variations just beneath the inner-core boundary, determined from the difference in travel time between waves reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
190
5
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(218 citation statements)
references
References 16 publications
22
190
5
1
Order By: Relevance
“…Tanaka and Hamaguchi, 1997;Niu and Wen, 2001;Waszek and Deuss, 2011;Miller et al, 2013) have been suggested to result from its bulk translation from west to east (Monnereau et al, 2010;Alboussière et al, 2010). In this scenario, the inner core melts on the leading eastern side, absorbing latent heat and producing a dense iron-rich fluid, and crystallises on the trailing western side, releasing latent heat and light elements into the overlying outer core.…”
Section: Introductionmentioning
confidence: 97%
“…Tanaka and Hamaguchi, 1997;Niu and Wen, 2001;Waszek and Deuss, 2011;Miller et al, 2013) have been suggested to result from its bulk translation from west to east (Monnereau et al, 2010;Alboussière et al, 2010). In this scenario, the inner core melts on the leading eastern side, absorbing latent heat and producing a dense iron-rich fluid, and crystallises on the trailing western side, releasing latent heat and light elements into the overlying outer core.…”
Section: Introductionmentioning
confidence: 97%
“…If large volcanic fields of lava or igneous provinces at the surface are restored to their eruption locations in a fixed frame of reference relative to plate motions, they concentrate above these two LLVPs (1). There also appears to be a correlation between the location of the LLVPs and anomalous velocity features present in the upper layers of the solid inner core (2). Thus, it appears that the heterogeneous structure of the lower mantle plays a role in the heat engine driving both the dynamo and plate tectonics; understanding images such as those displayed in Fig.…”
mentioning
confidence: 95%
“…Aubert et al (2008a) suggest that at least the cyclones beneath Asia may reach down to the inner core and increases the removal of heat and light elements from it's eastern hemisphere. This could help to explain why seismic waves that pass through the top hundred 100 km of this hemisphere are faster, more isotropic, and more attenuated (Tanaka and Hamaguchi 1997;Niu and Wen 2001;Yu and Wen 2006). Laboratory experiments have shown that the inner-core growth rate influences the structure of the hexagonal-closed-pack (hcp) inner-core iron: slower iron solidification favors wider spaced and more oriented dendritic growth (Bergman 2003).…”
Section: Mantle Controlmentioning
confidence: 99%